Empowering Female Prisoners Through Makeup and Hairstyling Training to Improve Skills and Economic Independence at the Semarang City Women’s Prison - Ifa Nurhayati; Erna Setyowati; Pramesti Adika Ratri (Universitas Negeri Semarang, 2025)
The issue of social reintegration and rehabilitation, particularly for women in correctional institutions (Lapas), remains a significant challenge in Indonesia. Female inmates often face negative stigma, limited access to education and skill training, and significant economic hardship upon release. Their unpreparedness for life outside often leads them to relapse into criminal behavior. Therefore, a strategic approach is needed that can provide skills and build their self-confidence, so they can live productively and sustainable in society. One skill that can be developed is hairdressing and makeup, which has broad market potential in Indonesia. With the increasing demand for beauty services, skills in this field not only open up job opportunities but can also become a sustainable independent business. Based on initial observations at Semarang City Prison, it was discovered that knowledge of certain skills was urgently needed, as the inmates had never received training in these areas. This community service program aims to utilize hairdressing and makeup skills, with a focus on creating more productive and sustainable skills, both during their sentence and after returning to society. This program is expected to build self-confidence and increase economic opportunities for women’s success, so they can become independent and useful individuals both inside and outside of prison. This training was held at the Semarang City Women’s Prison on May 8-9, 2025, and used lectures, reflection, practice, and evalution methods. The training results showed that the participants developed skills and high levels of motivation and received full support from the prison administration. The program provided economic resources, self-confidence, and opportunities for independent entrepreneurship as compensation after serving their sentence.